Review of the genus Odontomutilla Ashmead, 1899 (Hymenoptera: Mutillidae) of the Indian subcontinent, with description of two new species - Lelej, Arkady S.; Terine, Joshua B.; Kumar, Girish P.; Das, Dipanwita; Sureshan, Pavittu M. (Zootaxa, 2020)
Review of the 12 species and one subspecies of the genus Odontomutilla of the Indian subcontinent is provided. Two new species, O. sairandhriensis Terine, Girish Kumar & Lelej, sp. nov., ♀ (Kerala part of Southern Western Ghats) and O. fletcheri Lelej, Terine & Girish Kumar, sp. nov. ♀, ♂ (Sri Lanka), and the hitherto unknown male of O. trichocondyla (André, 1894) are described and illustrated. Mutilla indiga Bingham, 1908, ♂ (India: Uttar Pradesh) is transferred from the genus Odontomutilla to Smicromyrme Thomson, 1870 (comb. nov.). Odontomutilla speciosa (Smith, 1855), ♀ is excluded from the Indian subcontinent fauna as misidentified O. spectra (Bingham, 1908). Keys to the 12 species and one subspecies (males and females) of the genus are given.